Investigação da atividade muscarínica do veneno da serpente Micrurus lemniscatus (Linnaeus, 1758) em íleo isolado de cobaia - Marcela Cristine Silva (2013)
Despite of the great diversity of species in the genus Micrurus (Elapidae) in Americas, including Brazil, few studies have been done using the venom of these species or their purified toxins. Some neurotoxins present in these venoms act on muscarinic receptors involved in cholinergic neurotransmission. These toxins, called muscarinic toxins (6-8 kDa), are the most frequent molecules in venoms of M. lemniscatus. In the present work, we propose to make a screening of the muscarinic activity of the crude venom (CV) and of their semi-purified fractions on longitudinal smooth muscle (LSM) preparation of guinea pig ileum. The CV, assigned by Fundação Ezequiel Dias (FUNED, Belo Horizonte, Brazil), was fractionated by HPLC, using reverse phase or ionic exchange-CIEX, followed by reverse phase. The masses were evaluated by MALDI-TOF mass spectrometry and total protein was estimated according to the method of Lowry et al (1951). Segments of LSM of guinea-pig ileum were removed, suspended in isolated organ bath in Krebs-Ringer-Henseleit buffer, under aeration with carbogenic mixture. Isometric contractions elicited by CV or semi-purified fractions, were monitored in the presence of muscarinic antagonists (atropine, 4-DAMP and metoctramine). The muscarinic agonist carbachol (CCh) was used as a positive control. Thirty four semi-purified fractions were obtained from CV and 18 thereof, with molecular masses between 7-7,6 kDa were tested on LSM preparation. Concentrations of antagonists were defined according to the responses observed on standardization assays. CV, assayed in various concentrations (0,01; 0,03; 0,1; 0,3; 1; 3; 10 and 30 g/mL), induced a contraction of the LSM preparation, which was inhibited by atropine, metoctramine and 4-DAMP concentration of 10-9 M. Among the 18 tested semi-purified fractions in the following concentrations: 0,1; 0,3; 1; and 3 g/ml, only four of these fractions induced contraction of the preparation of LSM. Among them, two showed a toxin with the same molecular masses (7.232 kDa). The purified toxin, MT-Ml1 was tested in LSM. Cumulative curve were constructed with the following concentrations: 0.01, 0.03, 0.1 and 0.3 g/mL. The highest tested concentration (0.3 mg/mL) induced contraction of 27.25% (comparing to maximum contraction obtained by the charbacol) and was partially blocked when pre-incubated with atropine (10-9 M). In conclusion, the venom from M. lemniscatus presented agonist muscarinic activity, suggest the presence of muscarinic toxins, among them the MT-Ml1. This activity was antagonized by classical muscarinic antagonists. Studies are in progress to better identify the toxin MT-M11 and to determine their action mechanisms in LSM from guinea pig illeum. Indeed this venom seems to have several active molecules and represents a rich material to be studied and may provide good tools to study the muscarinic activity of nervous system.